Starptautiska zinātniska konference "Indivīds, sabiedrība un vara Baltijas reģiona vēstures lūzuma punktos": Konferences referātu tēzes, 2021. gada 14. un 15. oktobrī - (:unkn) unknown (Latvijas Universitāte, 2021)
Krājums apvieno konferencē “Indivīds, sabiedrība un vara Baltijas reģiona vēstures lūzuma punktos” nolasīto referātu tēzes. Latvijas, Lietuvas, Igaunijas un Polijas vēsturnieku, sociologu, teologu un juristu ziņojumos piedāvāts paraudzīties uz plašu parādību loku, kas bijušas novērojamas un ietekmējušas vēstures lūzuma punktus: sociālās kontroles mehānismu darbību, to daudzveidību un ietekmi uz indivīdu, sabiedrību un valsts politiku; etnisko grupu lomu, vietu Latvijā; Eiropas sava laika politisko centru un Latvijas teritorijas kontaktiem, to rezultātā radušos kultūras, prasmju un reliģisko strāvojumu mijiedarbību. Konference tiek organizēta un šīs tēzes sagatavotas VPP “Latvijas mantojums un nākotnes izaicinājumi valsts ilgtspējai”, projekta Nr. VPP-IZM-2018/1-0018 “Indivīda, sabiedrības un valsts mijiedarbība kopējā Latvijas vēstures procesā: vērtību konflikti un kopīgu vērtību veidošanās vēsturisku lūzumu posmos” ietvaros.

The collection includes the abstracts of the conference “Individual, Society, and Power at the Turning Points in the History of the Baltic Region”. The reports of historians, sociologists, theologians, and lawyers from Latvia, Lithuania, Estonia, and Poland offer a look at a wide range of phenomena that have been observed and influenced the turning points of history: the function of social control mechanisms, their diversity and their impact on individuals, society, and public policy; the role and place of ethnic groups in Latvia; the contacts of the political centres of Europe and the territory of Latvia, which resulted in the interaction of culture, skills, and religious currents. The conference is organised and this collection of abstracts is prepared in the framework of the State Research Programme “Latvian Heritage and Future Challenges for the Country’s Sustainability”, project No. VPP-IZM-2018/1-0018 “Interaction between the individual, the society, and the state in process of the history of Latvia: conflicting values and formation of shared values during historical turning points”.
Individual, Society, and Power at the Turning Points in the History of the Baltic Region : International scientific conference : Abstracts, Riga, 14–15 October 2021
Keywords: Baltijas reģiona vēsture; Indivīds; Sabiedrība; Vara; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History